Collection assessment for a Middle Eastern, English curriculum university library. (2nd July 2018) - Ho, Lilly Hoi Sze
Abstract : Purpose: Library collections at Middle Eastern universities have usually prioritized teaching over research resources. Zayed University is transitioning toward research, but research-centric collection assessments are rarely applied in the region. The purpose of this paper is to present on the successes and limitations of using citation analysis to assess the relevance of the Zayed University Library collection to its shifted focus. Design/methodology/approach: Recent Scopus-listed publications were sorted by the colleges of the Zayed University affiliated author, and citations listed in the publications were ranked as present or absent in the library collection. Findings: The resultant table provides an unambiguous evaluation of the extent to which the library collection has met the needs of recently successful published academics across disciplines. Pitfalls include the limitations of the Scopus database in representing all disciplines. Originality/value: Outcomes of the assessment enable the Library to develop collection strategies for continuous improvement and effectively support the campus researchers.